Electrochemiluminescence resonance energy transfer between methylene blue and Ru(bpy)32+-doped silica nanoparticles and its application in the "turn-on" detection of glucose. (29th May 2019) - Fu, Yuling; Qi, Wenjing; He, Hongkun; Zhao, Maoyu; Wu, Di; Qi, Lin; Li, Rong
Abstract : The ECL donor Ru(bpy)3 2+ -doped silica nanoparticles and acceptor methylene blue were applied in the electrochemiluminescence resonance energy transfer-based detection of glucose. Abstract : Herein, the electrochemiluminescence (ECL) donor Ru(bpy)3 2+ -doped silica nanoparticles (RuSiNPs) and acceptor methylene blue (MB) were combined to achieve electrochemiluminescence resonance energy transfer (ECRET) using the overlap of the ECL emission of RuSiNPs with the absorption of MB. Owing to the ECRET from RuSiNPs to MB, the ECL of RuSiNPs was quenched by MB. During the oxidation of glucose catalysed by MB only under an alkaline condition, MB with blue color is reduced to the colourless form methylene white by glucose; this is accompanied by the disappearance of absorbance at 650 nm. Accordingly, ECRET was inhibited after the addition of glucose to the RuSiNP and MB mixture. Therefore, the ECL "turn-on" detection of glucose was achieved via the proposed ECRET strategy. The proposed ECRET method exhibited high sensitivity for glucose detection with the limit of detection (LOD) of 85.4 nM, selectivity towards glucose in the presene of metal ions, anions, dopamine or uric acid, and fast response within 5 min; moreover, it was successfully applied for glucose detection in human serum samples, and the average recoveries of 99.33%, 99.73% and 100.07% were obtained. This widens the application of ECRET in bioanalysis.